Engaging academic staff in the quality assurance system in higher education: A field experiment - Meléndez-Jiménez, Miguel Ángel; Morales-Siles, Antonio José; Rodero-Cosano, Francisco Javier (Elsevier, 2022)
A randomised field experiment was conducted at the University of Malaga in 2017 to examine personalised norm-based messages’ effects on response rates to the annual faculty satisfaction survey. This research had a factorial design that combined formal versus informal writing styles with four norm-based messages: no norm, moral suasion, moral duty and social norm. The results reveal that two treatments – informal-moral duty and informal-social norm – both had the strongest positive effect. The university's quality assurance unit applied the informal-moral duty approach the following academic year, thereby increasing the overall response rate to the annual faculty satisfaction survey by 20% over the pre-intervention year.
Keywords: Ensayos de campo; Field experiment; Behavioural intervention; Quality assurance programme; Faculty satisfaction survey; Higher education; Personalised message; Nudging Norm-based; Moral suasion; Moral duty